2001
DOI: 10.1103/physrevc.63.065203
|View full text |Cite
|
Sign up to set email alerts
|

Low energy pion-hyperon interaction

Abstract: We study the low energy pion-hyperon interaction considering effective non-linear chiral invariant Lagrangians including pions, ρ-mesons, σ-mesons, hyperons and corresponding resonances. Then we calculate the S-and P -wave phaseshifts, total cross sections, angular distributions and polarizations for the momentum in the center-of-mass frame up to k = 400 MeV. With these results we discuss the CP violation in the Ξ → Λπ and Ω → Ξπ weak decays.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
49
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 30 publications
6
49
0
1
Order By: Relevance
“…Neglecting hyperon production in the hadronic phase, the dominant hadronic processes involving hyperons will be hyperon-π scattering. The scattering amplitude in general involves both scalar and vector channels [16]. One can show that global hyperon polarization from the vector channel is along while polarizations from the scalar channel and all the interferences are against the global quark polarization.…”
mentioning
confidence: 99%
“…Neglecting hyperon production in the hadronic phase, the dominant hadronic processes involving hyperons will be hyperon-π scattering. The scattering amplitude in general involves both scalar and vector channels [16]. One can show that global hyperon polarization from the vector channel is along while polarizations from the scalar channel and all the interferences are against the global quark polarization.…”
mentioning
confidence: 99%
“…in 1995 and his Ph.D.Thesis in 1991, on hyperon polarization [31], under the supervision of Prof. Hama. His work was motivated by a proposal by Prof. Hama and T. Kodama [32] that part of the (anti)hyperon polarization comes from its interaction with the medium that surrounds it.…”
Section: Contribution Of Prof Hama's Group To the Description Omentioning
confidence: 99%
“…1, 2 and 3. The expressions resulting from the calculations of the diagrams (and a review of the formalism) may be found in [13], where the sigma term was introduced simply as a parametrization. In recent studies [12], [14], it was shown that the σ term may be understood in terms of loops of pions, and then, in the calculation of the diagrams 1c, 2c and 3c, the expressions from [15], [16] have been used.…”
mentioning
confidence: 99%
“…Thus, this seems to be the most reliable treatment to be followed in studying the low energy πY interactions [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation